Experimental Evaluation of a Single Slope Solar Still - Santos Jaimes, Alfonso; Hernández Arroyo, Emil; Ramírez Jaimes, Zulma Y. (TECCIENCIA, 2017)
In Colombia, there exist regions where they have wells, public cells or rivers as water resource. For this reason, there is the need of developing and evaluating mechanisms that allows improve water physical, chemical and microbiological conditions, used for human consumption in these regions. This paper describes the operation, the energy balance, the construction and tests of a prototype of single-slope solar distiller used to determine the influence of temperatures, thickness of condenser and water level inside the collector on thermal efficiency of the process of water distillation. The prototype was tested on non- controlled environmental conditions at the city of Bucaramanga, measuring temperature, solar radiation and volume of distilled water. The trend lines gotten between volume of water distilled as a function of the incident solar radiation, the temperature difference between water and inner air in the distiller and between air and condenser on real operation condition, allowed the identification of optimal design parameters. After analyzing the results, it was observed a linear dependence between solar radiation and volume of water distilled, in addition to a dependence to the distilled volume to the difference of water temperatures, inner air and the condenser inside the distiller.